2020
DOI: 10.1016/j.catena.2020.104647
|View full text |Cite
|
Sign up to set email alerts
|

Palaeosols and their cover sediments of a glacial landscape in northern central Europe: Spatial distribution, pedostratigraphy and evidence on landscape evolution

Abstract: Knowledge of the distribution, types and properties of buried soils, i.e. palaeosols, is essential in understanding how lowlands in northern central Europe have changed over past millennia. This is an indispensable requirement for evaluating long-term human impact including soil erosion and land-cover dynamics. In the Serrahn area (62 km 2 ), a young glacial landscape representative for northeastern Germany and part of the Müritz National Park, 26 pedosedimentary sections were documented and analysed. To this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 115 publications
1
11
0
Order By: Relevance
“…800 BCE suggests the intensive use of oak lumber that resulted in a shift of the forest composition (Jahns, 2015). These results from archives in Brandenburg are in agreement with results of pollen and charcoal analyses from fossil soils in south Mecklenburg-Western Pomerania indicating the first human impacts on the vegetation during the Neolithic and an intensification during the Bronze Age; fire events started to increase roughly around the transition from the Bronze Age to the Iron Age (Kaiser et al, 2020). The present-day land cover in the surroundings of the royal tomb is dominated by arable land, pastures, and forests (European Environment Agency, 2020).…”
Section: Regional Settingsupporting
confidence: 87%
See 2 more Smart Citations
“…800 BCE suggests the intensive use of oak lumber that resulted in a shift of the forest composition (Jahns, 2015). These results from archives in Brandenburg are in agreement with results of pollen and charcoal analyses from fossil soils in south Mecklenburg-Western Pomerania indicating the first human impacts on the vegetation during the Neolithic and an intensification during the Bronze Age; fire events started to increase roughly around the transition from the Bronze Age to the Iron Age (Kaiser et al, 2020). The present-day land cover in the surroundings of the royal tomb is dominated by arable land, pastures, and forests (European Environment Agency, 2020).…”
Section: Regional Settingsupporting
confidence: 87%
“…One solution to reduce this error and thus possibly date newly discovered burial mounds more accurately would be the use of single-grain feldspar luminescence instead. Sandsized feldspar grains typically occur in various Quaternary deposits along the European sand belt (e.g., Füchtbauer and Elrod, 1971;Saye and Pye, 2006;Kalińska-Nartiša et al, 2015;Kalinìska et al, 2019), andReimann et al (2017) have shown that this novel method holds important advantages over quartz single-grain OSL in settings with a complex history of reworking. In a burial mound setting as presented in this study, it might be possible to reduce the age error to 6 %-7 % using single-grain feldspar luminescence.…”
Section: Opportunities and Challenges Of A Minimal Invasive Approach For Osl Dating Of Burial Moundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil cover is dominated by Albic Luvisols and Arenosols/Cambisols supplemented by Stagnosols, Gleysols and Histosols, which is a soil pattern typical for morainic sites in the region (Sommer et al 2008). In contrast with the intensive agricultural land surrounding the forest (Kappler et al 2018) and even with other forested sites in the region (Kaiser et al 2020), only marginal traces of past soil erosion have been detected at Kiecker thus far. The Kiecker forest belongs to the catchment of the Quillow River, which origins in Lake Parmener See on the southwestern border of the study site.…”
Section: Study Areamentioning
confidence: 97%
“…Similar humus horizons of that thickness in agriculturally used young glacial landscapes are often described as having developed from colluvic materials, although to be recognised as such they must demonstrate more obvious stratification and are located in places indicating slope deposits accumulation (e.g. Świtoniak, 2014Mendyk et al, 2016b;Kaiser et al, 2020). These earthen materials fit the criteria for thick heap material (PSC, 2019;Kabała et al, 2019) as it was removed from the pond intentionally, but not for agricultural purposes (e.g.…”
Section: Soil Genesis and Classificationmentioning
confidence: 99%